Selected legumes, roots & tubers and other cereals, September 2021 - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
This price bulletin was developed by researchers at IFPRI Malawi with the goal of providing clear and accurate information on the weekly variation of retail prices for selected agricultural commodities that are important for food security and nutrition in Malawi. The reports are intended as a resource for those interested in agricultural markets in Malawi.